La designación del sucesor en el antiguo reino de Macedonia - Fernández Nieto, Francisco Javier (Gerión. Revista de Historia Antigua, 2006)
The successor’s figure in the Temenid house tends in historical times to be established by means of the inheritance from fathers to sons. There are more possibilities for the first-born son of each marriage. It is impossible to establish if it was an original system that favours the brothers. The royal will is the rule that regulates successory order. Bearing in mind every antecedents, the Macedonian Assembly consolidated very simple rules for the alternation of the kings. The potential candidates receive a special education. The candidate who was called to be promoted, could be associated, with no title, into representatives, administratives and governmental functions.